Cover crops and controlled-release urea decrease need for mineral nitrogen fertilizer for cotton in sandy soil - Santos Cordeiro, Carlos Felipe dos [UNESP]; Rodrigues, Daniel Rodela; Echer, Fabio Rafael (Elsevier B.V., 2022)
Cover crops can affect nitrogen fertilization efficiency, soil nitrogen content, and cotton yield. However, the interaction effects of controlled-release nitrogen fertilizers, applied N rate, and cover crops on cotton growth, yield and fiber quality remains unknown, especially in sandy soils with low N content. Soil nitrogen and cotton growth, yield and fiber quality were evaluated as a function of different N rates and N sources in five rotation systems with or without cover crops, over four years. The treatments were: (1) cotton rotation crops (i.e., fallow, single grass, grass + grass, grass + legume and a mixture of cover crops), (2) nitrogen rates (70, 100 and 130 kg N ha(-1)), and (3) nitrogen sources (urea and controlled-release urea). Under a mixture of cover crops, fiber yields were 12% and 21% higher compared to the single grass and rotation fallow, respectively. Cotton in the fallow rotation required a higher rate of N (130 kg ha(-1)) than in rotation systems with cover crops (100 kg ha(-1)), in systems with cover crops to achieve the highest yields. Controlled-release urea reduced the demand for N fertilizer by 30% in the fallow. It also increased the content of soil N by 16% (mean of two seasons). Micronaire and fiber strength were lower with 130 kg ha(-1) of N. There is no need to increase nitrogen fertilization in cotton, as long as controlled-release urea and cover crops are employed, preferably mixtures of grasses and legumes.
Keywords: Crop rotation; Cover crops mixtures; Nitrogen sources; Fiber quality; N soil